Neo-Conservation of Biodiversity: A Review of International Endeavors - Shahzaib, Muhammad (Badan Pengembang Konservasi UNNES, 2020)
As the dawn of the industrial revolution has begun since the last few decades, it has produced a huge impact on the biodiversity of organisms on our blueish-green planet. The extent of this impact is increasing day by day due to the constant progression of technology and these maneuvers are pushing the biodiversity to its edge. Although, this constant progress has also modified our techniques and methodologies that we applied previously to prevent the overlap of both environmental and technological niches. But still, the imbalances on the natural scale posed to the biodiversity by our evolution are increasing gradually. This study gives us an insight into the present range and magnitude of international efforts and the interventions needed to protect biodiversity from an unrecoverable loss.